Meat, dairy and vegetable emulsions: Recent innovations in the development of functional, healthy and more stable foods - Espinoza-Leandro, Yuly Kety (2023)
Applications of formulations that incorporate emulsified oils offer interesting prospects for producing foods with better characteristics that are in line with the new trends in healthy eating and the new regulations on nutritional claims. This review defines and classifies the types of emulsions according to their drop size, formulation and analyzes the latest research related to the application of emulsions in the food industry. It presents valuable information on the use of micro, nano and macro emulsions for the preparation of meat, dairy and vegetable products as a potential alternative in the transport of bioactive compounds, reformulations with better lipid profiles and substitution ingredients of meat origin by ingredients of plant origin, obtaining foods with acceptable functional and sensory properties. New advances in the emulsion industry open up great possibilities in the delivery of health products, however, there are still limitations in the use of ingredients of plant origin in products formulated in considerable percentages with ingredients of animal origin. There are opportunities to improve the technology of food emulsion, the application at an industrial level is a step that is being taken little by little in congruence with the economic viability of the use of vegetable oils in the reformulation and the demand of current consumers for delivery of products with a clean label. It is suggested to study the economic feasibility of the industrial application of the use of single and double emulsion systems as a substitute ingredient for animal fats.